Makna Ungkapan Yesus “Aku Akan Datang Kembali” menurut Yohanes 14:3 - Etika Niat Laia; Gunar Sahari (Vieka Wahana Semesta, 2023)
Abstract: This research examines the meaning of the expression Jesus I will come again according to John 14:3 and its application to the church today. This is a great hope for Christians who believe because the promise of His return is a reality that will definitely happen. In this research, researchers used qualitative methods or literature review. And several conclusions were obtained as follows: First, Jesus' expression